Small Molecular Contaminant and Microorganism Can Be Simultaneously Detected Based on Nanobody-Phage: Using Carcinogen Aflatoxin and Its Main Fungal Aspergillus Section Flavi spp. in Stored Maize for Demonstration - Ren, Xianfeng; Yue, Xiaofeng; Mwakinyali, Silivano Edson; Zhang, Wen; Zhang, Qi; Li, Peiwu (Frontiers in Microbiology, 2020)
Simultaneous detection technology has been becoming a hot topic in analytical chemistry; however, very few reports on how to simultaneously detect small molecular contaminants and microorganisms have been in place. Aflatoxins are a group of highly toxic and carcinogenic compounds, which are produced mainly by Aspergillus flavus and A. parasiticus from section Flavi responsible for aflatoxins accumulation in stored cereals. Both aflatoxins and Aspergillus section Flavi were used to demonstrate the duplex real-time RCR method of simultaneously detecting small molecular contaminants and microorganisms. The detection of aflatoxins and Aspergillus section Flavi was carried out depending on the anti-idiotypic nanobody-phage V2-5 and aflatoxin-synthesis related gene nor-1 (= aflD), respectively. The quantitative standard curves for simultaneous detection of aflatoxins and Aspergillus section Flavi were constructed, with detection limits of 0.02 ng/mL and 8 × 102 spores/g, respectively. Naturally contaminated maize samples (n = 25) were analyzed for a further validation. The results were in good agreements between the new developed method and the referential methods (high performance liquid chromatography and the conventional plating counts).